2010
DOI: 10.1017/s003329171000173x
|View full text |Cite
|
Sign up to set email alerts
|

Economic downturns and population mental health: research findings, gaps, challenges and priorities

Abstract: Prior research suggests that the current global economic crisis may be negatively affecting population mental health. In that context, this paper has several goals: (1) to discuss theoretical and conceptual explanations for how and why economic downturns might negatively affect population mental health; (2) present an overview of the literature on the relationship between economic recessions and population mental health; (3) discuss the limitations of existing empirical work; and (4) highlight opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 52 publications
2
102
0
9
Order By: Relevance
“…Recently, they found that increases in suicide rates have been observed across European countries following the onset of the current recession 23. Consistent increases in male suicide rates have been noted in many other studies 24. The relationships between morbidity in mental health, health inequalities and recessions are less well understood and findings differ between studies 7 25.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, they found that increases in suicide rates have been observed across European countries following the onset of the current recession 23. Consistent increases in male suicide rates have been noted in many other studies 24. The relationships between morbidity in mental health, health inequalities and recessions are less well understood and findings differ between studies 7 25.…”
Section: Discussionmentioning
confidence: 91%
“…There are good grounds for thinking that this may be so, including consistent evidence that those who become unemployed during a recession may have worse mental health than those who do not [2]. Some studies have documented the direct effect of the economic recession on the general population’s mental health by comparing outcomes before and after the onset of the crisis [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since the onset of the global recession of 2008, several studies have suggested that it had, and continues to have, a negative impact in the population's mental health (Avcin et al, 2011;Meltzer et al, 2010;Uutela, 2010;Zivin et al, 2011). However, and although it is known that individuals with psychiatric diseases represent a particularly high risk group (Giotakos, 2010), data on previously remitted Major Depressive Disorder (MDD) patients are not available.…”
Section: To the Editormentioning
confidence: 99%